Identification of the immune checkpoint signature of multiple myeloma using mass cytometry‐based single‐cell analysis. Issue 5 (29th April 2020) - Wang, Jinheng; Zheng, Yongjiang; Tu, Chenggong; Zhang, Hui; Vanderkerken, Karin; Menu, Eline; Liu, Jinbao
Abstract: Objectives: New targets or strategies are needed to increase the success of immune checkpoint‐based immunotherapy for multiple myeloma (MM). However, immune checkpoint signals in MM microenvironment have not been fully elucidated. Here, we aimed to have a broad overview of the different immune subsets and their immune checkpoint status, within the MM microenvironment, and to provide novel immunotherapeutic targets to treat MM patients. Methods: We performed immune checkpoint profiling of bone marrow (BM) samples from MM patients and healthy controls using mass cytometry. With high‐dimensional single‐cell analysis of 30 immune proteins containing 10 pairs of immune checkpoint axes in 0.55 million of BM cells, an immune landscape of MM was mapped. Results: We identified an abnormality of immune cell composition by demonstrating a significant increase in activated CD4 T, CD8 T, CD8 + natural killer T‐like and NK cells in MM BM. Our data suggest a correlation between MM cells and immune checkpoint phenotypes and expand the view of MM immune signatures. Specifically, several critical immune checkpoints, such as programmed cell death 1 (PD‐1)/PD ligand 2, galectin‐9/T‐cell immunoglobulin mucin‐3, and inducible T‐cell costimulator (ICOS)/ICOS ligand, on both MM and immune effector cells and a number of activated PD‐1 + CD8 T cells lacking CD28 were distinguished in MM patients. Conclusion: A clear interaction between MM cells and the surrounding immune cells was established, leading to immune checkpoint dysregulation. The analysis of the immune landscape enhances our understanding of the MM immunological milieu and proposes novel targets for improving immune checkpoint blockade‐based MM immunotherapy. Abstract : In this study, we performed immune checkpoint profiling of bone marrow (BM) samples from multiple myeloma (MM) patients and healthy controls using mass cytometry. Our data suggest a correlation between MM cells and immune checkpoint phenotypes and expand the view of MM immune signatures. Specifically, several critical immune checkpoints, such as PD‐1/PD‐L2, galectin‐9/T‐cell immunoglobulin mucin‐3 and ICOS/ICOSL, on both MM and immune effector cells and a number of activated PD‐1 + CD8 T cells lacking CD28 were distinguished in MM patients, and they serve as novel targets for developing more potent and efficacious checkpoint blockade‐based MM immunotherapeutic strategies.